2023
DOI: 10.1002/pi.6493
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, polymerization and properties of an adamantyl‐based benzoxazine

Abstract: A novel adamantyl‐based benzoxazine (AD‐Bz) was successfully synthesized with 1,3‐bis(4‐aniline)‐adamantane (AD) derived from 1‐adamantanol and acetanilide through the Friedel–Crafts alkylation reaction. The chemical structure, curing behavior and curing kinetics of AD‐Bz were characterized by Fourier transform infrared spectroscopy, NMR spectroscopy (1H NMR and 13C NMR) and DSC, respectively. The results indicated that the activation energies (Ea) of AD‐Bz were 106.3 kJ mol−1 (Kissinger–Akahira–Sunose method)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The E' vs. temperature curves (a) and tan δ vs. temperature curves (b) of P(BPA-AD/dd1) main . [Color figure can be viewed at wileyonlinelibrary.com] of 253.4 C), 19 the main-chain polybenzoxazine (P(BPA-AD) main ) exhibited a higher T g due to its higher crosslinking density. Notably, P(BPA-AD 0.5) main , P(BPA-AD 0.25) main and P(BPA-dd1) main presented two temperature peaks in the loss factor (tan δ) vs. temperature curves.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations
“…The E' vs. temperature curves (a) and tan δ vs. temperature curves (b) of P(BPA-AD/dd1) main . [Color figure can be viewed at wileyonlinelibrary.com] of 253.4 C), 19 the main-chain polybenzoxazine (P(BPA-AD) main ) exhibited a higher T g due to its higher crosslinking density. Notably, P(BPA-AD 0.5) main , P(BPA-AD 0.25) main and P(BPA-dd1) main presented two temperature peaks in the loss factor (tan δ) vs. temperature curves.…”
Section: F I G U R Ementioning
confidence: 99%
“…Generally, there are three main methods for the reduction of the dielectric constants of benzoxazine resins: the first method is the introduction of fluorine atoms, 14,15 Si O bonds, 16 aliphatic rings/chains 2,17 and other low-polarity or bulk chemical structures into the three-dimensional network of polybenzoxazine through molecular design to obtain new structural benzoxazines with excellent dielectric properties. [18][19][20][21] For instance, Velez-Herrera et al synthesized highly fluorinated mainchain benzoxazine resins from highly fluorinated diamines, highly fluorinated bisphenol A, and formaldehyde. It was shown that the dielectric constant and dielectric loss of the fluorinated polybenzoxazine reached 2.2 and 0.008 @ 1 GHz, respectively, 15 which was attributed to the less polarizability and larger free volume of C-F bonds compared with C-H bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Li et al introduced crown ether into bisphenol A type polyimide, which effectively reduced the dielectric constant. 15 Yonekawa et al copolymerized p-tert-butylcalix [8]alkene glycidyl ether with benzoxazine to form a dense cross-linking network, which reduced the dielectric constant from 3.6 to 2.9 at 1 GHz. 16 The curing temperature of conventional benzoxazine is relatively high, which may have some impact on the practical applications of PBZ.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐polarity groups, such as fluorinated groups 4 and siloxane, 5 are introduced to decrease the molar polarizability of the polymers. The free volume of PBZ could be increased by incorporating steric hindrance groups, for instance, tert‐butyl 6,7 and adamantane, 8 thereby decreasing the polarized molecular density of PBZ. Yuan et al prepared a PBZ containing bulky tert‐butyl groups and low‐polarity siloxane chain to improve the thermal stability and low‐dielectric properties 9 .…”
Section: Introductionmentioning
confidence: 99%